Bootstrap confidence sets with weak instruments - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 2011)
We study several methods of constructing confidence sets for the coefficient of the single right-hand-side endogenous variable in a linear equation with weak instruments. Two of these are based on conditional likelihood ratio (CLR) tests, and the others are based on inverting t statistics or the bootstrap P values associated with them. We propose a new method for constructing bootstrap confidence sets based on t statistics. In large samples, the procedures that generally work best are CLR confidence sets using asymptotic critical values and bootstrap confidence sets based on LIML estimates.
Keywords: C10; C15; 330; weak instruments bootstrap; confidence sets; Vertrauen; Bootstrap-Verfahren